Relationship between muscle mass and neuromuscular function in the muscular strength of elderly women practicing and non-practicing physical activities (Research, Society and Development, 2021)
Objective. To verify the correlation between muscle mass and neuromuscular function in muscle strength of women practicing and not practicing physical activities. Methods. This is a cross-sectional study conducted with older women (60 and over), physically active (fa) and physically inactive (fi). The muscle strength of the upper limb (handgrip strength - hgs; resisfor test) and lower limb (30 second chair stand test) were evaluated; as well as muscle mass (calf circumference - cc); and neuromuscular activity (semg) of the following muscles: flexor carpi radialis (fcr) and biceps brachii (bb) (upper limb); vastus lateralis (vl), vastus medialis (vm) and tibialis anterior (ta) (lower limb). The student t test and multiple linear regression were used (95%; p